Imaginary and Reconstructed Antiquity by Andrea Mantegna and Filippino Lippi - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2013)
The article explores peculiar forms of antique quotations, first of all, the uses of the all’antica details in Andrea Mantegna and Filippino Lippi’s paintings. It appears that there is an opposition between Mantegna’s documental vision of antiquity and Lippi’s fantasy images. But in fact, there are traces of resemblance among both some of motives and approaches and the painters’ style developments of the later period, which were adopted by a number of the Cinquecento artists
Keywords: classical tradition; Italian painting; Early Renaissance art